Adaptabilidad transcultural de la orientación de estudiante a estudiante pare le adjuste academico - Brown, William F.; Garcia Hassey, Eduardo; Garcia Cortes, Fernando (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Evaluation of student-to-student academic adjustment counseling for freshmen attending Southwest Texas State University demonstrated that an experimental (counseled) sample excelled significantly a matching control (uncounseled) sample on all criteria of scholastic success. The criteria employed for evaluating counseling outcome included first-semester grade-point averages, as well as test-retest gain scores on the Survey of Study Habits and Attitudes and the Effective Study Test The testing and counseling materials developed for this program, were translated into Spanish and the student-counseling-student approach was adapted for use with Spanish- speaking students. Comparison of pre-counseling and post-counseling scores for a sample of first-year psychology students attending the Universidad Nacional Autónoma de México showed that these counselees also made significant gains in their measured study skills. Comparison of research results obtained from the English-language and Spanish-language projects suggests that the student-to-student counseling approach does have cross-cultural adaptability.